Znaki towarowe w sporcie = Trademarks in sports - Westfal, Krzysztof M. (Journal of Education, Health and Sport, 2015)
Westfal Krzysztof M. Znaki towarowe w sporcie = Trademarks in sports. Journal of Education, Health and Sport. 2015;5(12):666-677. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44781 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A666-677 https://pbn.nauka.gov.pl/works/695075 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015 Westfal Krzysztof M. Znaki towarowe w sporcie Trademarks in sports. Quality in Sport 2015;1(4):63-71. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Krzysztof M. Westfal Katedra Prawa Cywilnego, Handlowego i Ubezpieczeniowego Uniwersytet im. Adama Mickiewicza w Poznaniu Znaki towarowe w sporcie Trademarks in sports Streszczenie Przez uzyskanie prawa ochronnego na krajowy znak towarowy, rozumie się używanie znaku towarowego w sposób zarobkowy lub zawodowy na całym obszarze RP. Natomiast analogiczne uprawnienie wynikające z rejestracji wspólnotowego znaku towarowego, dotyczy stosowania znaku na terytorium całej Wspólnoty. Używanie znaku towarowego polega w szczególności na umieszczaniu tego znaku na towarach objętych prawem ochronnym lub ich opakowaniach, oferowaniu i wprowadzaniu tych towarów do obrotu, ich imporcie lub eksporcie, a także oferowaniu lub świadczeniu usług pod tym znakiem oraz posługiwaniu się takim znakiem w celu reklamy. W dobie wielkich pieniędzy, które bezsprzecznie rządzą dzisiejszym sportem, prawa ze znaków towarowych, obok praw do transmisji z wydarzeń sportowych, zyskują dla wszystkich sportowych jednostek organizacyjnych znaczenia kluczowego. Kluby, związki i federacje sportowe czerpią zyski z praw do znaków towarowych, głównie poprzez udzielanie przedsiębiorcom licencji na ich używanie. Proces ten najłatwiej zaobserwować przy okazji organizacji dużych wydarzeń sportowych. Jako cel badań niżej podpisany obrał wskazanie prawnych zasad zarządzania znakami towarowymi w sporcie, w obliczu ich ciągle rosnącego znaczenia. Publikacja obejmie prezentację sposób i zasady wykorzystywania zarejestrowanych już znaków sportowych przez sportowe jednostki organizacyjne, a także płynących stąd korzyści. Realizacja celu badawczego będzie dokonywana, przede wszystkim, przy zastosowaniu metody dogmatycznej. Analizie poddane zostaną akty prawa krajowego i unijnego. Podejmowana problematyka rodzi jednak konieczność uwzględnienia dorobku także innych nauk, zwłaszcza marketingu, biznesu i ekonomii. Wśród materiałów poddanych analizie, oprócz aktów prawa powszechnie wymienić należy także dane zgromadzonych w rejestrach znaków towarowych UP RP i OHIM. Za główny wniosek płynącym z niniejszego opracowania uznać należy konstatację, iż jakość w nowoczesnym sporcie przejawia się również, a w kwestii finansowej być może przede wszystkim, w jakości zarządzania znakami towarowymi. Abstract By getting the right protection for national trade mark, it is understood use of the mark for profit or for professional purposes throughout the territory of Poland. In contrast, a similar right conferred by a Community trade mark, concerns the application of the mark throughout the Community. Use of the mark is in particular the placement of the sign to the goods covered by the right of protection or their packaging, delivering and placing the goods on the market, import or export, as well as offering or providing services under that mark and the use of such a sign for advertising purposes. In the era of big money that undoubtedly govern the sport today, the law of trademarks, beside the rights to broadcast sporting events, gaining for all sporting significance of key organizational units. Clubs, associations and sports federations benefit from trademark rights, principally through the granting of licenses to entrepreneurs to use them. This process is most easily seen by the way the organization of major sporting events. As the aim of the research undersigned has chosen an indication of the legal rules governing trademarks in sports, in the face of ever increasing significance. The publication will include a presentation method and rules for the use of sports characters already registered by sports entities, as well as the benefits flowing from here. The implementation of the research will be carried out primarily by the method dogmatic. The analysis will be subject to national laws and EU. Taken the issue arises, however, need to take into account the achievements of other sciences, especially marketing, business and economics. Among the materials analyzed, in addition to the acts of commonly mention should also be stored in the data registers trademarks UP RP and OHIM. Behind the main conclusion flowing from this report should be regarded assertion that quality in modern sports, also manifests itself, and the financial aspects, perhaps above all, the quality of management of trademarks. Słowa kluczowe: OHIM, sport, prawo własności przemysłowej, Urząd Patentowy, znaki towarowe Keywords: OHIM, sport, industrial property rights, patent office, trademarks